2020
DOI: 10.1109/mim.2020.9289071
|View full text |Cite
|
Sign up to set email alerts
|

Network Measurements for Web Tracking Analysis and Detection: A Tutorial

Abstract: UPC), where he received the B.Sc. degree in Computer Science in 2008 and the M.Sc degree in Computer Architecture, Networks and Systems in 2010. He has several years of experience in network and system administration and currently holds a Projects Scholarship at UPC. His expertise and research interest are in computer networks, especially in the field of network monitoring, web tracking and anomaly detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…e larger the number, the larger the template (where 1 means the template is 5 × 5, 2 means the template is 15 × 15, and so on, 10 means the template is 95 × 95); it can be seen that the NDC and NCC measurements are less affected by the size of the template, while the NIADD and NIASD measurements are greatly affected by noise under the small template, which seriously affects the matching results. e experimental results show that the size of the noise and the size of the template affect the value of the similarity measure to varying degrees, and the use of a suitable similarity measure can resist these effects to a certain extent [20]. e method to eliminate the influence of noise is mainly to reduce or eliminate the noise in the image by detecting noise, filtering, and other means.…”
Section: E Source Of Noise and The Noise Model Of Domain Visionmentioning
confidence: 99%
“…e larger the number, the larger the template (where 1 means the template is 5 × 5, 2 means the template is 15 × 15, and so on, 10 means the template is 95 × 95); it can be seen that the NDC and NCC measurements are less affected by the size of the template, while the NIADD and NIASD measurements are greatly affected by noise under the small template, which seriously affects the matching results. e experimental results show that the size of the noise and the size of the template affect the value of the similarity measure to varying degrees, and the use of a suitable similarity measure can resist these effects to a certain extent [20]. e method to eliminate the influence of noise is mainly to reduce or eliminate the noise in the image by detecting noise, filtering, and other means.…”
Section: E Source Of Noise and The Noise Model Of Domain Visionmentioning
confidence: 99%
“…Users may voluntarily provide personal information on the web, such as filling out web forms, or such information may be indirectly collected without their knowledge through IP header analysis, HTTP request, search engine query analysis, JavaScript, etc [22]. However, recent studies have shown that the web tracking is widely used for malicious purposes, such as price discrimination, government surveillance, background scanning, and identity theft [24,35]. With the increasing use of the internet and digital technology, cyberattacks and surveillance have become more prevalent, posing significant threats to internet privacy and security: Malicious websites collect and sell user data to third parties without the user's knowledge or consent, which can lead to identity theft, financial fraud, and other harmful consequences.…”
Section: Introductionmentioning
confidence: 99%